The chest x-ray in acute bronchiolitis: technical quality, findings, and an assessment of its reliability - Juan Manuel Rius Peris; Ana Isabel Maraña Pérez; Ana Valiente Armero; Jorge Mateo Sotos; Leonor Guardia Nieto; Ana María Torres; Elisa María Cueto Calvo (Elsevier, 2021)
Introduction: Despite the recommendations of the current Clinical Practice Guidelines, the chest x-ray continues to be a widely used diagnostic test in the assessment of infants with acute bronchiolitis (AB). However, there have not been many studies that have assessed its reproducibility in these patients. In the present study, an evaluation is made on the radiographs, describing their quality, their radiological findings, and provides new evidence on the agreement between observers. Method: Out of a total of 281 infants admitted due to acute bronchiolitis, 140 chest x-rays were performed. Twelve doctors from different specialities evaluated the presence or absence of 10 radiological signs previously agreed by consensus. The level of agreement between 2 observers, and in groups of 3 or more, were analysed using the Cohen and Fleiss kappa index, respectively. Results: Only 8.5% of the radiographs showed evidence of a complicated AB. The between-observer agreement in groups of 3 or more was medium, and with little variability (kappa: 0.20−0.40). However, between 2 observers, specialists in radiology, the variability was wider, (kappa: −0.20 to 0.60). This level of agreement was associated with factors including, the sign to evaluate, the medical specialty, and level of professional experience. Conclusion: The low levels of agreement between observers and the wide variability, makes the chest x-ray an unreliable diagnostic tool, and is not recommended for the assessment of infants with AB. Resumen: Introducción: A pesar de las recomendaciones de las actuales Guías de Práctica Clínica, la radiografía de tórax sigue siendo una prueba diagnóstica ampliamente utilizada en la evaluación de lactantes con bronquiolitis aguda. No obstante, su reproductibilidad en estos pacientes no ha sido muy estudiada. En la presente investigación, se evalúan radiografías describiéndose su calidad técnica, hallazgos radiológicos en las mismas y se aportan nuevas evidencias sobre la concordancia entre observadores. Método: Sobre un total de 281 lactantes ingresados por bronquiolitis aguda, 140 radiografías de tórax fueron realizadas. 12 médicos de diferentes especialidades evaluaron la presencia o ausencia de 10 signos radiográficos previamente consensuados. El nivel de concordancia entre 2 observadores y en grupos de 3 o más, fue estudiado mediante el índice kappa de Cohen y de Fleiss respectivamente. Resultados: Únicamente en el 8,5% de las radiografías se evidenciaron signos de BA complicada. La concordancia entre observadores en grupos de 3 o más fue mediana y con escasa variabilidad (kappa: 0,20−0,40), sin embargo, entre 2 observadores, especialista con radiólogo de referencia, la variabilidad fue más amplia, (kappa: −0,20 to 0,60). Este nivel de concordancia se relacionaba con factores tales como el signo a evaluar, la especialidad médica y el grado de experiencia profesional, entre otros. Conclusión: Los bajos niveles de concordancia entre observadores y su amplia variabilidad, convierten a la radiografía de tórax en una herramienta diagnóstica poco fiable y no recomendable para la evaluación de lactantes con BA.